Modelling the spatial-temporal progression of the 2009 A/H1N1 influenza pandemic in Chile - Raimund Bürger; Gerardo Chowell; Pep Mulet; Luis M. Villada (Mathematical Biosciences and Engineering)
A spatial-temporal transmission model of 2009 A/H1N1 pandemic influenza across Chile,a country that spans a large latitudinal range, is developed to characterize the spatial variation in peak timingof that pandemic as a function of local transmission rates, spatial connectivity assumptions for Chilean regions, andthe putative location of introduction of the novel virus into the country. Specifically, ametapopulation SEIR (susceptible-exposed-infected-removed) compartmental model that tracks the transmissiondynamics of influenza in 15 Chilean regions is calibrated. The model incorporates population mobility among neighboringregions and indirect mobility to and from other regions via themetropolitan central region (``hub region''). The stability of the disease-freeequilibrium of this model is analyzed and compared with thecorresponding stability in each region, concluding that stability mayoccur even with some regions having basic reproduction numbersabove 1.The transmission model is used along with epidemiological data to explorepotential factors that could have driventhe spatial-temporal progression of the pandemic. Simulations and sensitivity analyses indicate that thisrelatively simple model is sufficient to characterize the south-north gradient in peak timing observed during the pandemic, and suggest that south Chile observed the initial spread of the pandemic virus, which is in line with a retrospective epidemiological study. The ``hub region'' in our model significantly enhanced population mixing in a short time scale.